2011
DOI: 10.1128/jb.05041-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Abyssomicin- and Proximicin-Producing Marine Actinomycete Verrucosispora maris AB-18-032

Abstract: Verrucosispora maris AB-18-032 is a marine actinomycete that produces atrop-abyssomicin C and proximicin A, both of which have novel structures and modes of action. In order to understand the biosynthesis of these compounds, to identify further biosynthetic potential, and to facilitate rational improvement of secondary metabolite titers, we have sequenced the complete 6.7-Mb genome of Verrucosispora maris AB-18-032.Verrucosispora maris AB-18-032 was isolated from a deep marine sediment sample collected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…L. gen. n. maris of the sea, denoting the source of the isolate). The description is based on data taken from this and previous studies Goodfellow and Fiedler 2010;Roh et al 2011). Aerobic, Grampositive, non-acid-fast actinomycete which forms an extensively branched, light to dark orange pigmented substrate mycelium on ISP media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. gen. n. maris of the sea, denoting the source of the isolate). The description is based on data taken from this and previous studies Goodfellow and Fiedler 2010;Roh et al 2011). Aerobic, Grampositive, non-acid-fast actinomycete which forms an extensively branched, light to dark orange pigmented substrate mycelium on ISP media.…”
Section: Discussionmentioning
confidence: 99%
“…This isolate, which has been provisionally labeled ''Verrucosispora maris'' (Goodfellow and Fiedler 2010), produces a family of novel polycyclic polyketides, the abyssomicins Riedlinger et al 2004;Keller et al 2007a, b) and proximicin A, an aminofuran type antibiotic ). In addition, it is known from the whole genome sequence of this organism that it contains around 23 biosynthetic gene clusters encoding for the production of known or predicted secondary metabolites (Roh et al 2011). Partial characterization of the abyssomicin-producing strain showed that it had chemotaxonomic and morphological properties similar to that of the type strain of V. gifhornensis, but could be distinguished from the latter using a combination of genotypic and phenotypic properties .…”
Section: Introductionmentioning
confidence: 98%
“…JS614, sequence accession CP000509, CP000508 [136] Saccharopolyspora spinosa NRRL 18395, sequence accession AEYC00000000 [137] Streptomyces griseoaurantiacus, sequence accession AEYX01000000 [138] Streptomyces griseus XyelbKG-1, sequence accession ADFC00000000 [139] Streptomyces sp. PP-C42, sequence accession AEWS01000000 [140] Verrucosispora maris AB-18-032, sequence accession CP002638, CP002639 [141] Phylum Chlamydiae Chlamydia pecorum E58, sequence accession CP002608 [142] Chlamydia psittaci 6BC, sequence accession CP002586 (chromosome), CP002587 (plasmid) [143] Chlamydia psittaci Cal10, sequence accession AEZD00000000 [143] Chlamydophila psittaci RD1, sequence accession FQ482149 (chromosome) FQ482150 (plasmid) [144] Standards in Genomic Sciences…”
Section: Phylum Tenericutesmentioning
confidence: 99%
“…One of these compounds, abyssomicin, is isolated from Verrucosispora maris AB-18-032 [52]. It demonstrates antibacterial properties by inhibiting para-aminobenzoic acid biosynthesis [8,53].…”
Section: Antimicrobial Properties Of Novel Antibioticsmentioning
confidence: 99%